Cellular and molecular characterization of atherothrombosis-related markers in sprague dawley rats fed with high cholesterol diet supplemented with herbal extracts - Kwaifa, Ibrahim Kalle (2021)
Atherothrombotic cardiovascular diseases are the most common cause of death worldwide. Although antiplatelet, anticoagulant, simvastatin and other related drugs globally prescribed for these disorders have been available, some are commonly associated with several adverse effects. Intervention with natural-based preparation has been recognized as an alternative. This study utilised a combination of herbal extracts for the treatment of atherothrombosis in Sprague Dawley (SD) rats fed with a high cholesterol diet (HCD). The study investigated the therapeutic potentials of herbal extracts; a combination of Zingiber officinale (ginger), Allium sativum (garlic), Citrus Limon (lemon), Malus Domestica (Apple)/ apple cider vinegar and Honey (ZACAH) on cellular and molecular atherothrombosis-related markers in SD rats fed with HCD. Identification of the related phytochemicals present in ZACAH extracts was performed by ultra-high performance liquid chromatography-mass spectrophotometry (UHPLC-MS) profiling at both negative and positive models. Thirty-six male SD rats were randomly divided into six groups. The normal diet (ND), HCD, treatment with simvastatin (TRTSM) at 10mg/kg of body weight (BW), treatment with ZACAH extracts (TRT1) at 1mg, 3mg (TRT2), and 5mg (TRT3) per kilogram of BW. At the end of the 12 weeks of experiments, the rats were sacrificed, and the collected blood was subjected to serum lipid profile, protein expressions, and platelet ultrastructural analysis by scanning electron microscope (SEM). The atherogenic index (AI) and % protection were calculated based on the results obtained from the lipid profile. SEM was also used to examine the aorta endothelial ultrastructural changes. The aorta and liver tissues were utilised for histopathological examinations by haematoxylin & eosin (H & E) and Masson’s trichrome (MT) stains. The tissues were also processed for the mRNA expression profiling of lipid metabolism atherothrombosis-related genes, endothelial prothrombotic and coagulation related genes, and the genes of the fibrinolytic system. Ten related phytochemical compounds present in ZACAH extracts were identified, including gingerol (retention time (RT); 18.62, compounds %; 5.6), hesperidin (11.19, 12.1), naringin (10.07, 13.1), sulindac (13.96, 9.7), scoparone (15.86, 8.0), hesperetin (11.18, 12.1), rutin (9.90, 13.2), limonin (17.87, 6.2), carboxylic acid (3.30, 18.9) and citric acid (2.18, 20). Increased BW and food intake were recorded in all the experimental groups, while a significant difference was observed in the HCD group compared to ND, TRTSM and ZACAH extracts treatment groups (p<0.05). The total cholesterol (TC), triglycerides (TG) and low-density lipoprotein (LDL) levels were significantly increased, and a decrease in high-density lipoprotein (HDL) was observed in the HCD group compared to ND, TRTSM and ZACAH extracts treatment groups (p<0.05). Significant differences were observed in the AI of HCD compared to ND and ZACAH extracts treatment groups (p<0.05). The % protection was improved at TRTSM (18%), TRT1 (55.6%), TRT2 (59.7%), and TRT3 (72.8%) in dose-dependent manner. The SEM analysis revealed organized atherothrombosis, smooth muscle cells proliferation in the intima, and significantly activated platelets in the HCD group. Histopathological examinations revealed a significant increase in the intima-media ratio, marked increase in collagen fibres and intense hepatic steatosis in the HCD group compared to ND, TRTSM and ZACAH extracts treatment groups (p<0.05). The mRNA expression of lipid metabolism genes, including 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMG-CoA-R), proprotein convertase subtilizing Kexin-9 (PCSK-9) and sterol regulatory element-binding protein-2 (SREBP-2) were upregulated while the expression of low-density lipoprotein-receptor (LDL-R) gene was downregulated in the HCD compared to ND, TRTSM and ZACAH extracts treatment groups (p< 0.05). The proteins levels of nitric oxide (NO) and tissue-type plasminogen activator (t-PA) were significantly downregulated while the tissue factor (TF) and plasminogen activator inhibitor-1 (PAI-1) protein concentrations were upregulated in the HCD group compared to ND, TRTSM and ZACAH extracts treatment groups (p<0.05). The mRNA expression of endothelial prothrombotic, coagulation related genes and the genes of the fibrinolytic system, including TF, PAI-1 and thrombin-activatable fibrinolysis inhibitor (TAFI) were upregulated, whereas the expression of endothelial nitric oxide synthase (eNOS), tissue factor pathway inhibitor (TFPI) and t-PA genes were downregulated in the HCD group compared to ND, TRTSM and ZACAH extracts treatment groups (P<0.05). No significant difference was recorded between ZACAH extracts treatment groups, ND and TRTSM treatment groups at p<0.05. The extent of the relationship between related proteins and genes expression profile determined by bivariate Pearson’s product-moment correlation coefficient (r) was positively correlated across the groups. The findings suggested that ZACAH extracts supplementation could ameliorate the dysfunctional endothelial, activated platelet, hepatic steatosis and molecular atherothrombotic changes in SD rats fed with HCD, and could be considered a potential candidate for the treatment of hyperlipidaemia-related atherothrombotic cardiovascular diseases.